Application of histone modification-specific interaction domains as an alternative to antibodies - Kungulovski, Goran; Kycia, Ina; Tamas, Raluca; Jurkowska, Renata Z.; Kudithipudi, Srikanth; Henry, Chisato; Reinhardt, Richard; Labhart, Paul; Jeltsch, Albert (Genome Research, 2014)
Post-translational modifications (PTMs) of histones constitute a major chromatin indexing mechanism, and their proper characterization is of highest biological importance. So far, PTM-specific antibodies have been the standard reagent for studying histone PTMs despite caveats such as lot-to-lot variability of specificity and binding affinity. Herein, we successfully employed naturally occurring and engineered histone modification interacting domains for detection and identification of histone PTMs and ChIP-like enrichment of different types of chromatin. Our results demonstrate that histone interacting domains are robust and highly specific reagents that can replace or complement histone modification antibodies. These domains can be produced recombinantly in Escherichia coli at low cost and constant quality. Protein design of reading domains allows for generation of novel specificities, addition of affinity tags, and preparation of PTM binding pocket variants as matching negative controls, which is not possible with antibodies.
10.1101/gr.170985.113